The Impact of Nutritional Status and Tumor-Infiltrating Lymphocytes (CD4+ and CD8+) on Chemotherapy Response in Colorectal Cancer Patients - Lukman K; Septianto R; Rudiman R; Ruchimat T; Sribudiani Y; Nugraha P; Primastari E; Budiman D (Cancer Management and Research)
Kiki Lukman,1 Rhandy Septianto,1 Reno Rudiman,1 Tommy Ruchimat,1 Yunia Sribudiani,2 Prapanca Nugraha,1 Etis Primastari,3 Deny Budiman1 1Surgery Department, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 3The Hasan Sadikin Hospital’s Anatomical Pathology Department in Bandung, Bandung, IndonesiaCorrespondence: Kiki Lukman; Rhandy Septianto, Email kiki.lukman@unpad.ac.id; rhandy21001@mail.unpad.ac.idIntroduction: The World Health Organization reports that colorectal cancer (CRC) is the second leading cause of cancer-related mortality globally, with an estimated 1.9 million new cases annually. Tumor-infiltrating lymphocytes (TILs) are frequently associated with colorectal cancer and are believed to play a significant role in the immune response to cancer cells. Regarding chemotherapy responses in patients with colorectal cancer, this study aims to investigate the association between nutritional status and infiltrating lymphocyte counts, specifically CD4+ and CD8+.Materials and Methods: This prospective observational study analyzed the impact of nutritional status using body mass index (BMI) and TILs levels (CD4+/CD8+) on chemotherapy outcomes in CRC patients treated at a tertiary hospital in West Java, Indonesia, from July 2023 to June 2024.Results: Thirty-six research subjects were included. Eighteen participants had high levels of TILs CD4+ and CD8+ expression. Nutritional status, age, histological type, tumor site, stage, and metastasis showed no significant correlation with the expression of either CD4+ or CD8+. Nutritional status, levels of CD4+ and CD8+ were significantly associated with chemotherapy responses in CRC patients (p< 0.001).Conclusion: Nutritional status and elevated TIL levels (CD4+/CD8+) positively correlate with better chemotherapy response in CRC patients.Plain Language Summary: Colorectal cancer is the second leading cause of cancer-related deaths worldwide, with 1.9 million new cases reported annually, according to the World Health Organization. This study focuses on understanding how nutrition and immune system activity affect chemotherapy responses in patients with colorectal cancer in Indonesia. The immune system plays a vital role in fighting cancer, and certain immune cells, called tumor-infiltrating lymphocytes (TILs), may help the body combat colorectal cancer. Specifically, we looked at two types of these immune cells, CD4+ and CD8+, and their connection to patients’ nutritional health during chemotherapy. We investigated 36 colorectal cancer patients receiving chemotherapy at a tertiary hospital in West Java, Indonesia, between July 2023 to June 2024. The results showed a link between better nutritional status and higher levels of CD4+ and CD8+ immune cells with improved responses to chemotherapy. These findings highlight the importance of supporting patients’ nutritional health during cancer treatment and suggest that monitoring immune cell activity could help predict treatment success. By tailoring care to these factors, healthcare providers may be able to improve outcomes for people with colorectal cancer.Keywords: chemotherapy response, colorectal cancer, prognostic, tumor infiltrating lymphocytes